DETERMINAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN DI INDONESIA - Cahyaningrum, Rasita Isnaini; Setiawati, Erma (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study aims to analyze the Determinants of Timeliness of Financial Report Submission in Companies in Indonesia. The object of this study is the property and real estate sector for the period 2019-2023. The variables in this study consist of profitability, leverage, liquidity, audit committee and Timeliness of Financial Report Submission. Quantitative approach with financial reports as the data and collected as many as 80 samples with 16 companies for a period of 5 years. The data collection technique uses purposive sampling and logistic regression analysis as its static analysis. The findings show that profitability has a significant positive effect on the timeliness of financial report submission while leverage, liquidity, and audit committee do not have a significant effect on the timeliness of financial report submission. Management must ensure that the company complies with the reporting deadline provisions set by the Financial Services Authority (OJK) and other authorities. And companies with healthy profitability may need to pay more attention to cash flow and debt management so that the reporting process is not disrupted by urgent financial problems.